TEACHER'S AND STUDENT'S NEEDS FOR MATHEMATICAL PROBLEMS IN DISASTER CONTEXT - Nuzulidar Nuzulidar; Rahmah Johar; Sulastri Sulastri (Jurnal Infinity, 2019)
Indonesia is an archipelagic country lies on the Pacific Ring of Fire, resulting in the country being vulnerable to disaster. Teachers need to accustom students to manage natural disaster situation in a more logical approach. Therefore, it is necessary to develop mathematical problems in disaster contexts. This research is an early stage of developmental research. The purpose of this study was to analyze the needs of teachers and students of mathematical problems in disaster contexts. The participants in this study were a mathematics teacher and 53 Year 7 and 8 students at one of the public junior high school, located in a Tsunami affected area, in Banda Aceh. Data collection involved an open questionnaire, and data analysis was carried out descriptively. The results showed that the teacher often provided mathematical problems in learning but had never read mathematical problems in disaster contexts. Also, only three students had ever read such problems. The results also revealed that nearly half of the students (41.5%) liked to solve mathematical problems. Besides, both the teacher and 71.7% of the students agreed and were willing to participate in the learning process involving mathematical problems in disaster contexts. The results of the study also showed that the mathematical questions in disaster contexts were limited. Thus, it is necessary to develop mathematical problems in disaster contexts.